PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA KARTU BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II DI SDN SEMERU 1 KOTA BOGOR - Rizky Eka Mahardika; Indriyani; Hoiriah; Damita Anatasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by number card media on the mathematics learning outcomes of second-grade students at SDN Semeru 1 Kota Bogor in the topic of place value. The research problem is based on the low understanding of place value concepts and the dominance of conventional teaching methods in the classroom. This study employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest design. The research subjects consisted of 25 students. The instruments used were pretest and posttest questions that had been validated by experts. The results showed an increase in the average score from 45.23 to 75.18 with a gain score of 64.89%, which is categorized as high. The t-test showed a t-value of 12.456 with a p-value of 0.000 (< 0.05), indicating a significant difference between the pretest and posttest results. The use of concrete media in the form of number cards effectively helped students understand abstract mathematical concepts, while the PBL model was able to increase active student engagement in the learning process. The findings conclude that the combination of PBL and number card media can significantly improve mathematics learning outcomes while providing a meaningful and contextual learning experience. Therefore, active, innovative, and contextual learning approaches are recommended to be implemented in primary school mathematics learning.